Recurrent destabilising paediatric pelvic arterial haemorrhage: Choosing the embolisation technique that works – A case report. (July 2019) - Ng, Bobby KW; Kumar, A; Wong, Jeffrey KT
A 12-year-old male child presented with a history of fall from three floors height with a stable pelvic fracture but destabilised haemodynamically soon after from pelvic arterial haemorrhage. Two attempts of selective embolisation controlled the haemorrhage transiently but recurrent pelvic arterial haemorrhage ensued jeopardising patient's haemodynamic status. Pelvic arterial haemorrhage was ultimately controlled by a unilateral non-selective embolisation of anterior and posterior divisions of internal iliac artery without any immediate or long-term ischaemic complications. Unilateral non-selective transcatheter arterial embolisation in paediatric pelvic arterial haemorrhage may be used as a viable management option with the potential of evading ischaemic complications and effective in selective embolisation failures.